Can I still trust you, my dear doll? A philosophical and legal exploration of smart toys and trust. Issue 2 (4th May 2019) - Keymolen, Esther; Van der Hof, Simone
ABSTRACT: The purpose of this article is to show how the smartification of children's toys impacts the concept of trust. We make use of the 4Cs conceptual trust framework – context, construction, curation, codification – to analyse how the technological, commercial and legal developments central to the arrival of the Internet of Toys have an impact on the trust relations of children, parents and the companies behind smart dolls. We found that the introduction of smart dolls brings forth several trust issues. First, important vulnerabilities, such as monitoring practices and data-sharing, take place beyond the awareness of children and parents. Even if they try to read the terms and conditions or look into the technical specifications of the toys, these products remain black boxes because the operating systems are proprietary and not all information is disclosed or understandable. Second, with the arrival of smart dolls, a form of hybrid ownership arises. Because of the networked character of the dolls, they remain under the influence and control of the company. Children and parents have to trust the companies not to abuse this connection. And finally, the regulatory framework that should protect children is not only inadequate, it might actually exacerbate trust issues.